Electric Field and Space Charge Distribution in Propylene Carbonate Under Continuous DC Electric Field using Kerr Effect - Z. N. Zakaria; M. S. Laili; N. A. Rahman; P. L. Lewin; T. Andritsch; N. Hussin (Iranian Journal of Electrical and Electronic Engineering)
The study investigates the electric field and space charge distributions in propylene carbonate under direct current (DC) applied fields using Kerr effect. Propylene carbonate is known for its high permittivity and is utilised in many applications, including electrochemical systems and dielectric materials. Understanding the behaviour of electric fields and space charge distributions within propylene carbonate is critical for optimising its performance in these applications. In the study, Kerr effect is employed which by applying the DC electric field across the test liquid for measuring the electric field and space charge distributions within the propylene carbonate. The experimental setup involved a controlled application of DC fields, and the Kerr effect measurements were conducted using an optical system. The results show significant understandings into the behaviour of space charges and their influence on the electric field distribution in propylene carbonate. Distinct patterns of charge accumulation and electric field distortion were observed and analysed in the dielectric liquid properties and charge transport mechanisms. The relationship between electric fields and space charges in propylene carbonate under DC conditions has been provided by the findings. The study also shows that the Kerr effect is a useful tool for studying electric field distributions in complex materials.